Synthesis and characterization of calcium hydroxide obtained from agave bagasse and investigation of its antibacterial activity - Chávez Guerrero, Leonardo; Garza Cervantes, Javier Alberto; Caballero Hernández, Diana Elia; González López, Rodrigo; Sepúlveda Guzmán, Selene; Cantú Cárdenas, María Elena (2016)
Calcium hydroxide (Ca(OH)2) is recognized as an efficient bactericide and is widely applied as a root canal filler in endodontic treatment. Ca(OH)2 is mainly produced by hydration of calcium oxide (CaO), a product of the thermal decomposition of calcium carbonate (CaCO3) from sources such as limestone. In this work, calcium hydroxide particles were synthetized by the thermochemical transformation of waste biomass from the tequila industry. Agave biomass processed at 600 °C was composed mostly of calcium carbonate (CaCO3), while calcination at 900 °C followed by hydration produced Ca(OH)2. The morphology and crystalline nature of the Ca(OH)2 particles were characterized by micro-Raman spectroscopy, scanning electron microscopy and X-ray diffraction analysis. Bactericidal activity of synthesized calcium hydroxide was evaluated with the agar diffusion assay. Our results provide evidence that Ca(OH)2 obtained from agave biomass is an effective bactericidal against Escherichia coli and Enterococcus faecalis. Biomass from agave is available in Mexico and the rest of the American continent, the use of processed bagasse for medical applications could provide a venue for the useful disposition of industrial waste.